A Comparative HRQOL Study of High Cost and Low Cost Anti-Diabetic Products - A, Radhakrishna; P, Umadevi; T, Vedavathi; S, Naresh; K.S.K, Upadhyayula; A, Mythili; Rao P, Rajeswara; Ratna J, Vijaya (Indian Journal of Pharmacy Practice)
Purpose: This study aims to compare high cost and low cost anti-diabetic products by a HRQOLstudy. Methods: This is a cross-sectional, prospective, observational study carried out in a private endocrinology clinic which purchases medicines at a low cost and dispenses them free of cost to the patients. In the private out-patient clinic, medicines are prescribed by the doctor and purchased by patients. The patients purchase them from a pharmacy adjacent to the clinic and these medicines are comparatively of higher cost than the medicines given in a government hospital. The study group includes 117 randomly selected patients using anti-diabetic medicines of high cost and 115 randomly selected patients using low cost medicines. These patients were interviewed using SF-36, and their HRQOL values were recorded. The patients were counseled for three months by trained pharmacy students, with the help of printed brochures that explains the diet, dietary intake measures, dietary restrictions, daily exercise. At the end of three months, their HRQOLwas recorded again. Results: Pre-counseling, the low cost medicine users have a significantly lower mean HRQOL in all the domains and in total HRQOL, when compared to the high cost medicine users. The patient counseling effort has shown a significant improvement in the HRQOL values of all the domains of both high cost and low cost anti-diabetic medicines. However, the mean HRQOL values of the low cost medicine users were still significantly lesser than the high cost medicine users in most of the domains. Conclusion: In general, users of low cost products of selected medicines showed a lesser HRQOL than the high cost products of the same medicines. Patient counseling resulted in improving the HRQOLvalues of all the patients in all the groups.
Keywords: Anti-diabetic drugs; HRQOL; Patient counseling; Quality of Life